BAHASA BALI SEBAGAI SENTRAL KEBUDAYAAN BALI - I Made Suweta (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
Language has a connection with culture. Language as a social activity is part of culture.Language is a legacy of society and part of a very important community tradition, function,position and benefits. Until now there has not been found a society that is however simple itsculture without having a language. Language is a cultural tool that is also an integral elementof culture. In this paper three issues will be discussed, namely: (1) how is the description ofBalinese language in general?, (2) how is the nature and elements of Balinese culture ?, and (3)how is the relationship between Balinese and Balinese culture? Based on the discussion conducted,it can be confirmed that the conclusions of this paper are as follows: (1) language is a freesymbolic vocal system that is used by community members to communicate; (2) language is thebest tool for communication; (3) language has a close connection with culture; (4) language asa social activity is part of culture; (5) the culture of a society has a part (subsystem) whichincludes the language subsystem; (6) Balinese language which is part of Balinese culture aswell as the center of culture; (7) Balinese language is a legacy of the community and part of theBalinese tradition which is very important function, position, and benefits.